Effects of D-cycloserine on extinction of mesolimbic cue reactivity in alcoholism: a randomized placebo-controlled trial - Kiefer, Falk; Spanagel, Rainer; Mann, Karl; Vollstädt-Klein, Sabine (Psychopharmacology, 2015)
Rationale: Mesocorticolimbic reactivity to alcohol-associated cues has been shown to be associated with relapse to renewed drinking and to be decreased by cue-exposure-based extinction training (CET). Evidence from preclinical studies suggests that the extinction of conditioned alcohol-seeking behavior might be facilitated by drugs increasing N-methyl-d-aspartate (NMDA) receptor-associated memory consolidation. Objectives: In this study, we assessed the efficacy of CET treatment supplemented with the partial NMDA-receptor agonist d-cycloserine (DCS) at reducing mesolimbic cue reactivity (CR), craving, and relapse risk in alcoholism. Methods: In a randomized, placebo-controlled, double-blind study, we recruited 76 recently detoxified abstinent alcohol-dependent patients. Thirty-two (16 DCS, 16 placebo) patients showed cue-induced ventral-striatal activation measured with functional magnetic resonance imaging (fMRI) prior to treatment and were thus included in the efficacy analyses. After inpatient detoxification, patients underwent nine sessions of CET spaced over 3 weeks, receiving either 50 mg DCS or placebo 1 h prior to each CET session. FMRI was conducted before treatment and 3 weeks after treatment onset. Results: Following treatment with CET plus DCS, cue-induced brain activation in the ventral and dorsal striatum was decreased compared to treatment with CET plus placebo. Elevated posttreatment ventral striatal CR and increased craving (assessed using the Obsessive Compulsive Drinking Scale) were associated with increased relapse risk. Conclusions: DCS was shown to augment the effect of CET for alcohol-dependent subjects. The interaction between craving and ventral-striatal CR on treatment outcome suggests that CET might be especially effective in patients exhibiting both high craving and elevated CR.
Gesehen am 24.01.2018